Protein Retention and Organoleptik Characteristic of Broiler Meat by Adding Sour Soy Milk in Drinking Water (1-5 Weeks) - Ida Ayu Okarini; Anak Agung Sagung Putu Kartini; Martini Hartawan (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2009)
This research was carried out to study effect sour soy milk in drinking water on protein retention of bdy chich and organoleptic test broiler cooked meat. The Completely Randomized Design (CRD)  were used which considered of three treatment and four replicates. Each refricate consists of five chickens. The treatments are as follow: A as control of drinking water not added sour soy milk; B 1% of sour soy milk in 1 liter drinking water (B = 83.3 g sour soy milk + 916.7 ml water) and C 2% of sour soy milk in 1 liter drinking water (C = 166.7  sour soy milk + 833.3 ml water). Sour soy milk contains total lactic acid bacteria (LAB) 8.98 x 104 – 1.96 x 106 cfu/g with pH 5.00 – 5.06. Sour soy milk made with natural fermentation (18 hours) at room temperature (30-32oC), no added starter culture LAB. Commercial diets concentrate type CP 511 (for starter phase 1-3 weeks) and type CP 512 for finisher phase 3-5 weeks. Drinking water was gien ad libitum. Crude protein body chick analyzed used ICW method and organoleptic test (Larmond, 1977) with hedonic scale (9.0 like – 1.0 dislike). Statistically analyzed by Anova (Gomez and Gomez, 1995) to significant different on the treatment. This results showed that B and C treatment no significant effect on protein retention, but the quantitative higher 10.53% and 13.16% than A treatment (protein retention = 38.9%). Its also C treatment higher 2.38% than B treatment. Organoleptic test by 20 judgement showed increasing like value: arome, texture, flavour, and overall acceptance on B and C treatment than control (A) treatment. Colour like meat not different on three treatment.In conclusion of the reserach effect sour soy milk 2% treatment on drinking water (1-5 weeks), showed that increase of organoleptic value aroma like and overall acceptance than control treatment, and also increasing protein retention body chick.   Keywords : Sour soy milk, protein retention body chick, organoleptic